Clinical profile of patients with prosthetic heart valve thrombosis undergoing fibrinolytic therapy and NYHA class as a predictor of outcome - Sanjeev Bhatia; Sharad Jain; Vishal Sharma; Zeeshan Mansuri; Krutika Patel; Pragya Jain; Mithilesh Kulkarni; Tanmay Agrawal; Kamal Sharma (Publisher: Shahid Beheshti University of Medical Sciences)
Background: Prosthetic heart valve thrombosis (PHVT) is a potentially fatal complication of heart valve replacement with mechanical prostheses mainly due to thrombosis.Aim: The study aimed to evaluate the clinical profile of the patients presenting with PHVT undergoing fibrinolytic therapy and analyzing patients with respect to New York Heart Association (NYHA) functional class on presentation and its association with outcome of fibrinolytic therapy.Settings & design: This was prospective, observational study conducted from June, 2016 to April, 2017. Total 133 patients with prosthetic heart valve thrombosis were included. Materials and methods: Routine blood investigations included complete hemogram, liver and renal function tests. Prothrombin time with INR was done on admission. The diagnosis of PHVT was assessed by fluoroscopy and/or echocardiography (transthoracic/transesophageal). Follow-up at 6 months was scheduled for all patients.Statistical analysis: Parametric values between two groups were performed using the independent sample t-test or chi-square test, as appropriate. Univariate and multivariate logistic regression was used to find out factors associated with outcome.Results: All patients received fibrinolytic therapy in which 108 (81.2%) were treated with streptokinase and 25 (18.8%) were treated with urokinase. On presentation, 48.9% patients were in NYHA class III, 41.4% in NYHA class IV and 9.77% in NYHA class II. Fibrinolytic therapy was successful in 105 patients (78.9%) and it failed in 28 patients (21.1%). Mortality in NYHA class II was 0%, NYHA class III was 4.6% and in NYHA class IV was 23.6%. During 6 months follow up prosthetic heart valve thrombosis recurred in 12 (11.43%) patients.Conclusion: From our single centre experience, fibrinolytic therapy is fairly effective first line therapy for prosthetic heart valve thrombosis and NYHA functional class on presentation can predict the outcome of fibrinolytic therapy.